2009
DOI: 10.1089/vim.2009.0047
|View full text |Cite
|
Sign up to set email alerts
|

Early Replication in Pulmonary B Cells After Infection with Marek's Disease Herpesvirus by the Respiratory Route

Abstract: Natural infection with Marek's disease virus occurs through the respiratory mucosa after chickens inhale dander shed f r o m i n fected c h i c k e n s . The early events in the lung following exposure to the feather and squamous epithelial cell debris containing the viral particles remain unclear. In order to elucidate the virological and immunological consequences of MDV infection for the respiratory tract, chickens were infected by intratracheal administration of infective dander. Differences between suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 49 publications
(40 reference statements)
1
51
0
Order By: Relevance
“…Thus, it is tempting to speculate that the vIL-8 chemokine might recruit B cells to the initial site of infection in the lung. Furthermore, the well-known delay in disease progression in the absence of B cells, e.g., upon bursectomy, underscores that B cells play a central role during early infection (3,33). The lack of B-cell recruitment in v⌬MetvIL-8-infected chickens could explain the reduced viral load in chickens infected via the natural route.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is tempting to speculate that the vIL-8 chemokine might recruit B cells to the initial site of infection in the lung. Furthermore, the well-known delay in disease progression in the absence of B cells, e.g., upon bursectomy, underscores that B cells play a central role during early infection (3,33). The lack of B-cell recruitment in v⌬MetvIL-8-infected chickens could explain the reduced viral load in chickens infected via the natural route.…”
Section: Discussionmentioning
confidence: 99%
“…In the respiratory tract, virus is likely taken up by macrophages and/or dendritic cells that transport the virus to the primary lymphoid organs; however, infected B cells can be detected in the lung as early as 2 days postinfection (3). Upon transport to the primary lymphoid organs, MDV efficiently replicates in B cells and subsequently infects activated CD4 ϩ T cells that carry the virus to the feather follicle epithelium, where infectious virus is produced and shed into the environment.…”
mentioning
confidence: 99%
“…The RM1 strain replicated extensively in the lung and infected the cells lining the parabronchi and within the pulmonary interstitium. The pattern of expression of pp38 in the lung of chickens inoculated with RM1 resembled those after infection with oncogenic strains (Purchase, 1970;Adldinger & Calnek, 1973;St Hill et al, 2004;Baaten et al, 2009). Purchase (1970) detected MDV antigens in epithelial cells lining the air capillaries of lungs 5 days after intra-abdominal inoculation with various oncogenic MDV strains.…”
Section: Discussionmentioning
confidence: 95%
“…St Hill et al (2004) detected the DNA of an oncogenic MDV in lungs of chickens following 3, 5, 7, and 10 d.p.i. Baaten et al ( 2009) demonstrated infection of macrophages and B cells in the lung of chickens infected intratracheally with oncogenic MDV. The nature of cells supporting infection with oncogenic and attenuated serotype 1 MDV is still unknown, and further studies using double-staining techniques like immunofluorescence/immunohistochemistry or in situ hybridization will be needed.…”
Section: Discussionmentioning
confidence: 97%
“…It was in chickens that the existence of the bursa of Fabricius (BF) and the B-cells that specialise in antibody production within it was first described [21]. Avian B-cells are crucial for inducing antibody responses against viral pathogens; in response viruses that infect birds often target B-cells to avoid elimination [22,23]. One such pathogen of veterinary and economic significance is infectious bursal disease virus (IBDV) which infects and subsequently causes cell death of developing B-cells as part of a mechanism to avoid elimination from the host [23][24][25].…”
Section: Introductionmentioning
confidence: 99%